Chelas Valley and Coina Wetlands Agricultural Parks - Manuela R Magalhães; João Silva; Manuel Leitão; Andreia Saavedra; Ana Müller (Fábos Conference on Landscape and Greenway Planning, 2013)
Over 70% of Europe’s population now lives in urban areas (EEA, 2006) and there is a substantial rural-urban migration causing a rapid expansion of the peri-urban interface, where domestic and industrial modifications of the environment interact strongly with agricultural production (Brook & Davila, 2000). Portugal, as the rest of Western Europe, has been through a profound process of urbanization beyond former city limits over the past decades, and even in regions where the population is decreasing, urban areas are still growing (Piorr, Ravetz & Tosics, 2011). As the urban pattern gradually distanced itself from the traditional compact city model, the urban fabric became scattered and fragmented, unfolding itself at the expense of the surrounding rural landscape (EEA, 2006). Today, the non-built areas take on a major importance in metropolitan areas planning process. As urban life demands the existence of open green spaces to contribute for the quality of the urban environment and the wellbeing of the population, urban voids are essential to the implementation of green corridors and ecological networks. In order to materialize these networks, there is a need to design also at site scale and the creation of agricultural parks reveals itself as a significant strategy, which integrates production, recreation and conservation functions and applies the principles contained in the European and international recommendations, including the European Sustainable Cities Report (European Commission, 1996), which states that the objectives of sustainability are more easily achievable acting from small areas, and involving the communities most directly concerned. If food production is a permanent function of urban and peri-urban agriculture, it is above all its multifunctional role that matters to address through the latest advances at a conceptual level, framed from the perspective of sustainable urban development. This paper aims to provide a framework for the design and implementation of two agricultural parks – Chelas valley and Coina wetlands – embedded in the context of municipal ecological networks. Both projects correspond to the preliminary study phase and were recently carried out in the Landscape Architecture Research Centre “Prof. Caldeira Cabral” of the Technical University of Lisbon (CEAP / UTL). The Chelas Valley project had its origin on an initiative of Lisbon’s municipality, while the Coina Wetlands agricultural park saw its beginning in the scope of the European project “Naturba – Interreg IV-B SUDOE”, whose purpose is to develop urban sustainable projects on cities fringes in order to overcome land use conflicts.
Keywords: greenways; chelas valley; coina wetlands; agriculture; park; europe